2010
DOI: 10.1038/nsmb.1923
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the unfolding of anthrax lethal factor by protective antigen oligomers

Abstract: The protein transporter, anthrax lethal toxin, is comprised of protective antigen (PA), a transmembrane translocase, and lethal factor (LF), a cytotoxic enzyme. Following assembly into holotoxin complexes, PA forms an oligomeric channel that unfolds LF and translocates it into the host cell. We report the crystal structure of the core of a lethal toxin complex to 3.1-Å resolution; the structure contains a PA octamer bound to four LF PA-binding domains (LFN). The first α helix and β strand of each LFN unfold an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
249
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(268 citation statements)
references
References 60 publications
19
249
0
Order By: Relevance
“…The staphylococcal ␣-hemolysin has been shown to form heptamers but under certain conditions will also form hexameric rings (25). Anthrax toxin was long thought to form heptamers exclusively (9), but the work by Krantz and colleagues (10,11,26,27) has shown that functional octamers can also be formed, a conclusion that is confirmed and extended by these studies. This suggests a cautionary approach when considering the oligomeric states of other anthrax-like toxins, such as clostridial C2 toxin and iota toxin (28), and even all other pore-forming toxins, to include consideration that alternative oligomeric forms might be present in certain situations.…”
Section: Discussionsupporting
confidence: 64%
“…The staphylococcal ␣-hemolysin has been shown to form heptamers but under certain conditions will also form hexameric rings (25). Anthrax toxin was long thought to form heptamers exclusively (9), but the work by Krantz and colleagues (10,11,26,27) has shown that functional octamers can also be formed, a conclusion that is confirmed and extended by these studies. This suggests a cautionary approach when considering the oligomeric states of other anthrax-like toxins, such as clostridial C2 toxin and iota toxin (28), and even all other pore-forming toxins, to include consideration that alternative oligomeric forms might be present in certain situations.…”
Section: Discussionsupporting
confidence: 64%
“…The overall shape of the translocon has been validated using both 2D and ultimately 3D electron microscopy. [2][3][4][5] Low resolution reconstructions obtained by single particle analysis of EM images of negatively stained specimens verified the prediction that coordinated unfolding and refolding forms a long hollow stem between the globular ''cap'' of the PA and the membrane. Preliminary EM structures suggest that the lumen of the pore is not a smooth featureless surface.…”
Section: Introductionmentioning
confidence: 94%
“…10 A minor fraction of PA 63 forms an octamer, which is less capable of forming channels, more robust in serum, and less cytotoxic. [11][12][13] In the cytoplasm, LF and EF exert different deleterious effects on cells. [14][15][16][17] Isolation of cytosolic and membrane fractions of time-course samples from intoxicated macrophages revealed that EF remained bound to the membrane fraction, while LF was found in the cytosolic fraction.…”
Section: Introductionmentioning
confidence: 99%